Repeated vs. Acute Exposure of RAW264.7 Mouse Macrophages to Silica Nanoparticles: A Bioaccumulation and Functional Change Study - Anaëlle Torres (Nanomaterials, 2020)
Synthetic amorphous silica is used in various applications such as cosmetics, food, or rubber reinforcement. These broad uses increase human exposure, and thus the potential risk related to their short- and long-term toxicity for both consumers and workers. These potential risks have to be investigated, in a global context of multi-exposure, as encountered in human populations. However, most of the in vitro research on the effects of amorphous silica has been carried out in an acute exposure mode, which is not the most relevant when trying to assess the effects of occupational exposure. As a first step, the effects of repeated exposure of macrophages to silica nanomaterials have been investigated. The experiments have been conducted on in vitro macrophage cell line RAW264.7 (cell line from an Abelson murine leukemia virus-induced tumor), as this cell type is an important target cell in toxicology of particulate materials. The bioaccumulation of nanomaterials and the persistence of their effects have been studied. The experiments carried out include the viability assay and functional tests (phagocytosis, NO and reactive oxygen species dosages, and production of pro- and anti-inflammatory cytokines) using flow cytometry, microscopy and spectrophotometry. Accumulation of silica nanoparticles (SiO2 NP) was observed in both exposure scenarii. However, differences in the biological effects between the exposure scenarii have also been observed. For phagocytosis, NO production and Tumor Necrosis Factor (TNF) release, repeated exposure tended to induce fewer effects than acute exposure. Nevertheless, repeated exposure still induces alterations in the macrophage responses and thus represents a scenario to be tested in detail.